Audiovisual speech perception: A new approach and implications for clinical populations - Irwin, Julia; DiBlasi, Lori (Language and Linguistics Compass, 2017)
This selected overview of audiovisual (AV) speech perception examines the influence of visible articulatory information on what is heard. Thought to be a cross-cultural phenomenon that emerges early in typical language development, variables that influence AV speech perception include properties of the visual and the auditory signal, attentional demands, and individual differences. A brief review of the existing neurobiological evidence on how visual information influences heard speech indicates potential loci, timing, and facilitatory effects of AV over auditory only speech. The current literature on AV speech in certain clinical populations (individuals with an autism spectrum disorder, developmental language disorder, or hearing loss) reveals differences in processing that may inform interventions. Finally, a new method of assessing AV speech that does not require obvious cross-category mismatch or auditory noise was presented as a novel approach for investigators.
Keywords: dept.psy

Teaching and learning guide for audiovisual speech perception: A new approach and implications for clinical populations. - Irwin, Julia; Turcios, Jacqueline (Language and linguistics compass, 2017)
Keywords: dept.psy

The development of gaze to a speaking face. - Irwin, Julia; Brancazio, Lawrence; Volpe, Nicole (The Journal of the Acoustical Society of America, 2017)
When a speaker talks, the visible consequences of what they are saying can be seen. Listeners are influenced by this visible speech both in a noisy listening environment and even when auditory speech can easily be heard. While visible influence on heard speech has been reported to increase from early to late childhood, little is known about the mechanism that underlies this developmental trend. One possible account of developmental differences is that looking behavior to the face of a speaker changes with age. To examine this possibility, the gaze to a speaking face was examined in children from 5 to 10 yrs of age and adults. Participants viewed a speaker's face in a range of conditions that elicit looking: in a visual only (speech reading) condition, in the presence of auditory noise (speech in noise) condition, and in an audiovisual mismatch (McGurk) condition. Results indicate an increase in gaze on the face, and specifically, to the mouth of a speaker between the ages of 5 and 10 for all conditions. This change in looking behavior may help account for previous findings in the literature showing that visual influence on heard speech increases with development.
Keywords: *Facial Expression; *Fixation, Ocular; *Speech Acoustics; *Speech Perception; *Visual Perception; *Voice Quality; Acoustic Stimulation; Acoustics; Age Factors; Audiometry, Speech; Child; Child, Preschool; Cues; Early-to-late; Facial Expression; Female; Fixation, Ocular; Humans; Male; Noise; Noise/ae [Adverse Effects]; Perceptual Masking; Photic Stimulation; Physics; Speech; Speech Acoustics; Speech Perception; Speech in noise; Speech reading; Video Recording; Visible speech; Visual Perception; Voice Quality; Young Adult; age; association; auditory stimulation; child; dept.hls; dept.psy; eye fixation; facial expression; female; human; male; masking; noise; photostimulation; preschool child; speech; speech audiometry; speech perception; videorecording; vision; voice; young adult

A familiarization protocol facilitates the participation of children with asd in electrophysiological research - Turcios, Jacqueline; Cook, Barbara; Irwin, Julia; Rispoli, Taylor; Landi, Nicole (JoVE (Journal of Visualized Experiments), 2017)
This paper includes a detailed description of a familiarization protocol, which is used as an integral component of a larger research protocol to collect electroencephalography (EEG) data and Event-Related Potentials (ERPs). At present, the systems available for the collection of high-quality EEG/ERP data make significant demands on children with developmental disabilities, such as those with an Autism Spectrum Disorder (ASD). Children with ASD may have difficulty adapting to novel situations, tolerating uncomfortable sensory stimuli, and sitting quietly. This familiarization protocol uses Evidence-Based Practices (EBPs) to increase research participants' knowledge and understanding of the specific activities and steps of the research protocol. The tools in this familiarization protocol are a social narrative, a visual schedule, the Premack principle, role-playing, and modeling. The goal of this familiarization protocol is to increase understanding and agency and to potentially reduce anxiety for child participants, resulting in a greater likelihood of the successful completion of the research protocol for the collection of EEG/ERP data.
Keywords: dept.cmd; dept.psy

Electrophysiological Indices of Audiovisual Speech Perception in the Broader Autism Phenotype. - Irwin, Julia; Avery, Trey; Turcios, Jacqueline; Brancazio, Lawrence; Cook, Barbara; Landi, Nicole (Brain sciences, 2017)
When a speaker talks, the consequences of this can both be heard (audio) and seen (visual). A novel visual phonemic restoration task was used to assess behavioral discrimination and neural signatures (event-related potentials, or ERP) of audiovisual processing in typically developing children with a range of social and communicative skills assessed using the social responsiveness scale, a measure of traits associated with autism. An auditory oddball design presented two types of stimuli to the listener, a clear exemplar of an auditory consonant-vowel syllable /ba/ (the more frequently occurring standard stimulus), and a syllable in which the auditory cues for the consonant were substantially weakened, creating a stimulus which is more like /a/ (the infrequently presented deviant stimulus). All speech tokens were paired with a face producing /ba/ or a face with a pixelated mouth containing motion but no visual speech. In this paradigm, the visual /ba/ should cause the auditory /a/ to be perceived as /ba/, creating an attenuated oddball response; in contrast, a pixelated video (without articulatory information) should not have this effect. Behaviorally, participants showed visual phonemic restoration (reduced accuracy in detecting deviant /a/) in the presence of a speaking face. In addition, ERPs were observed in both an early time window (N100) and a later time window (P300) that were sensitive to speech context (/ba/ or /a/) and modulated by face context (speaking face with visible articulation or with pixelated mouth). Specifically, the oddball responses for the N100 and P300 were attenuated in the presence of a face producing /ba/ relative to a pixelated face, representing a possible neural correlate of the phonemic restoration effect. Notably, those individuals with more traits associated with autism (yet still in the non-clinical range) had smaller P300 responses overall, regardless of face context, suggesting generally reduced phonemic discrimination.
Keywords: Article; Audiovisual speech perception; Broader autism phenotype; Development; ERP; audiovisual aid; audiovisual equipment; audiovisual speech perception; autism; behavior; broader autism phenotype; child; clinical article; dept.cmd; dept.hls; dept.psy; development; electrophysiology; female; human; male; participant observation; phenotype; social adaptation; social competence; speech perception; stimulus; vision test